1998
DOI: 10.1103/physrevb.58.6386
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic critical behavior of the Ising model on fractal structures

Abstract: International audienceThe critical temperature and the set of critical exponents (β,γ,ν) of the Ising model on a fractal structure, namely the Sierpiński carpet, are calculated from a Monte Carlo simulation based on the Wolff algorithm together with the histogram method and finite-size scaling. Both cases of periodic boundary conditions and free edges are investigated. The calculations have been done up to the seventh iteration step of the fractal structure. The results show that, although the structure is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
62
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 29 publications
2
62
0
1
Order By: Relevance
“…More information about their approach can be found in [57,64]. Other results are available [47,62] but differ from the results of [58] by comparitively minor amounts and do not affect the qualitative conclusions of the comparison with our bounds.…”
Section: Jhep03(2015)167mentioning
confidence: 64%
See 3 more Smart Citations
“…More information about their approach can be found in [57,64]. Other results are available [47,62] but differ from the results of [58] by comparitively minor amounts and do not affect the qualitative conclusions of the comparison with our bounds.…”
Section: Jhep03(2015)167mentioning
confidence: 64%
“…Initially this seems unlikely, as generic fractal spaces are expected to break translation invariance even in the continuum limit. Nevertheless, such systems do show critical behaviour at finite temperature, and so there have been multiple attempts to compare the Wilson-Fisher critical exponents with those of fractals, with mixed results [47]. Furthermore, it has been suggested that certain fractals [48][49][50] (those with small lacunarity) do recover translational invariance in the continuum.…”
Section: Jhep03(2015)167mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on renormalization methods, it has been shown that a second-order phase transition at nonzero temperature occurs only if the fractal substrate has an infinite ramification order. Moreover, since translational symmetry is a necessary condition to proceed with dimensional perturbation [3], the disagreement between the critical exponents determined by current methods [6,7,8,9,10,11] and those obtained by continuation of ε−expansions to noninteger dimension [12] can be related to the topological features of the fractal structure.…”
mentioning
confidence: 99%